INVESTIGATION OF ANTHELMINTIC EFFECT OF NEOLAMARCKIA CADAMBA FRUIT EXTRACTS IN ASCARIASIS - KAUR, KULDEEP; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2021)
Objective: Investigation of Anthelmintic effect of Neolamarckia Cadamba fruit extracts (Ethanol, Aquaous, Phenyl ether, Chloroform) in Ascariasis. Methods: The experiment was conducted on an adult Indian earthworm, Eiseniafoetida, owing of its morphological and physiological similarities to the human intestine roundworm parasite. Six sets of six earthworms were discharged sequentially into different extracts of N. cadamba fruits at dose levels of 5,10,15,20, and 25 mg/ml, respectively, and 25 mg/ml of albendazole solutions. Albendazole was employed as the standard reference medication. Results: The results showed that Ethanolic extract has the greatest degree of activity. When compared to any other extract or conventional medicine, it produces a paralytic effect sooner and has a shorter time to death (Albendazole). An ethanol extract included alkaloid, saponin, tannins, flavonoids, proteins, and amino acids. As a result, it is possible to infer that the ethenolic fruit extract of Neolomarckia Cadamba showed much more anthelmintic activity against Indian earthworms than the usual treatment (Albendazole). Conclusion: The solvents Ethanol, Chloroform, Phenyl Ether, and Aquaous were used to extract the Neolamarckia Cadamba. The results showed that Ethanolic extract has the greatest degree of activity. When compared to any other extract or conventional medicine, it produces a paralytic effect sooner and has a shorter time to death (Albendazole).